Intervenciones de Enfermería en los programas de prevención y control de epilepsia en Latinoamérica - Cudco Llangarì, Johanna Maribel (2025)
Epilepsy, a chronic disease that affects millions of people worldwide, including Latin America, requires comprehensive strategies for its control and prevention. Nursing interventions play a fundamental role in these programs as an essential component of care in health services. This bibliographic review aims to analyze the scientific evidence available on nursing interventions in epilepsy prevention and control programs in Latin American countries. A search was conducted in databases such as PubMed, Scielo, Dialnet, Redalyc, Elsevier, and national and international organizations. Keywords and Boolean search terms were used to identify relevant studies. The results were analyzed by triangulation, including a comparative analysis of the studies considered. It was identified that nursing interventions can have a positive impact on the prevention and control of epilepsy in Latin America. These interventions contribute to improving knowledge and understanding of epilepsy among affected people, their families, and the community, as well as improving the quality of life of the affected people. It also aims to promote adherence to pharmacological and non-pharmacological treatment and reduce the incidence of epileptic seizures, improving the quality of life of people with epilepsy and their families. Scientific evidence supports the fundamental role of nursing interventions in the prevention and control of epilepsy in Latin America. It is recommended that nursing training programs in the region for epilepsy be strengthened and that comprehensive quality care for patients be ensured.